Regional Government Responsibility as A Controlling Shareholder in The Collapse of BPR Aceh Utara - Jafar, M.; Adli, M.; Jauhari, Iman; Arifin, Khairani; Rahmah, Siti (Jurnal IUS Kajian Hukum dan Keadilan, 2025)
The North Aceh Regency Government established BPR Aceh Utara as a means of public service for PAD sources. BPR Aceh Utara runs a conventional business in accordance with the Banking Law. In 2018, the Aceh Government formed the Qanun LKS, which stipulates that financial institutions operating in Aceh are based on Sharia Principles. In OJK Letter Number: S-29 / KO.05011 / 2018, it is emphasized that all financial institutions in Aceh are required to switch from conventional to sharia, the Qanun LKS. However, BPR Aceh Utara cannot be transferred to the sharia system because the North Aceh Government, as the Controlling Shareholder, did not make capital participation and restructuring, so that its business license was revoked by the OJK with its decision Number KEP-27 / D.03 / 2024 concerning the Revocation of BPR Aceh Utara Business License. This is very detrimental to customers, employees, local governments, and the community. This study uses normative and empirical legal research methods, incorporating a statutory approach, a conceptual approach, and a comparative approach. Data collection was carried out through library research, including an analysis of primary, secondary, and tertiary legal materials as well as non-legal sources. Additionally, field research was carried out through interviews with respondents and informants who can provide relevant information about BPR Aceh Utara. The results of the study indicate that: First, efforts to improve the health of BPR Aceh Utara are not optimal because the Controlling Shareholder does not make capital participation as determined by the OJK and regulated in the Qanun on Capital Participation. Second, legal protection for customers is carried out by LPS by making savings payments that meet the requirements. Third, the Regional Head as the Controlling Shareholder is not responsible for the bankruptcy of BPR Aceh Utara. It is recommended that the regional head strengthen capital, foster BUMD management so that they are able to provide public services and PAD income.